Molecular Detection of Ureaplasma Urealyticum in Pregnant Woman Suffering from Urinary Tract Infection (The International Journal for Scientific Research, 2024)
Mycoplasma is a genus of bacteria that lack a cell wall, The present study was designed to identify the Ureaplasma urelyticium which causes the pregnant women suffering uti. The study included 200 samples of 150 pregnant women and 50 controls from the Bint Al-Huda teaching Hospital and Al-Haboubi teaching Hospital in the Thi-Qar provainc. The presence of the GPO gene in urine samples by using the PCR used as an indicator for mycoplasma colonization of urinary tract of pregnant, then the species was detected by DNA sequencing. in this study Regarding the GPO gene most of the cases were carry mycoplasmas and majority of the control groups expressing the positive results so that there was no significant statistical differences where (p value = 0.069). The present results recorded that the presence of about  94% homology between studied samples with Ureaplasma urelyticium sequences. Twenty-one, 12 and 6 genetic variations of 16SrRNA gene were identified in Mycoplasma hominis, Mycoplasma, ureaplasma urelyticium. Some variations were variably distributed in the majority of the studied samples. The study showed that the ureaplasma urelyticium.is an important cause of UTI in pregnant women in Iraqi population.
Keywords: pregnancy; urinary tract infection; mycoplasma; Ureaplasma urelyticium